2021
DOI: 10.1001/jamanetworkopen.2021.19600
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Goals of Youths in Canada Receiving Medication-Assisted Treatment for Opioid Use Disorder

Abstract: IMPORTANCEIn the literature on opioid use disorder (OUD), opioid abstinence is used as an outcome measure for individuals receiving medication-assisted treatment (MAT), without consideration of patient-reported goals (PRGs).OBJECTIVES To identify common PRGs for youths receiving MAT for OUD and assess whether these patients achieve their stated goals. DESIGN, SETTING, AND PARTICIPANTSThis prospective cohort study examined data from 152 individuals aged 16 to 25 years (noninclusive) recruited between May 22, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Importantly, these findings from service providers resonate with studies that have been done with youth using opioids and other drugs [13,18,21,23,24]. Youth in many settings have articulated their challenges accessing environments that are adultoriented [13,21], engaging in treatments that apply a 'one-size fits all' ideology [23], and that do not reflect their unique goals and preferences [18,[22][23][24]37]. This suggests that service providers and youth may have similar priorities during their point-of-care interactions.…”
Section: Ideas Themes a Community Select Representative Idea(s) Bmentioning
confidence: 64%
See 3 more Smart Citations
“…Importantly, these findings from service providers resonate with studies that have been done with youth using opioids and other drugs [13,18,21,23,24]. Youth in many settings have articulated their challenges accessing environments that are adultoriented [13,21], engaging in treatments that apply a 'one-size fits all' ideology [23], and that do not reflect their unique goals and preferences [18,[22][23][24]37]. This suggests that service providers and youth may have similar priorities during their point-of-care interactions.…”
Section: Ideas Themes a Community Select Representative Idea(s) Bmentioning
confidence: 64%
“…To better respond to the unique needs of youth, service providers suggested numerous solutions, such as engaging youth in service/treatment planning, providing youth with programs that help them maintain meaningful connections (i.e., positive relationships, cultural connection, and recreational activities), and creating services that are youth-specific. Importantly, these findings from service providers resonate with studies that have been done with youth using opioids and other drugs [13,18,21,23,24]. Youth in many settings have articulated their challenges accessing environments that are adultoriented [13,21], engaging in treatments that apply a 'one-size fits all' ideology [23], and that do not reflect their unique goals and preferences [18,[22][23][24]37].…”
Section: Ideas Themes a Community Select Representative Idea(s) Bmentioning
confidence: 71%
See 2 more Smart Citations
“…16 Additionally, a study examining the association between OUD treatment goals and factors associated with their attainment among AYA in Canada found that those receiving MMT were more likely to decrease their dose 3 months after treatment initiation (odds ratio = 4.42, 95% confidence interval [CI]: 1.40 to 14.0) in comparison to those receiving buprenorphine. 17 This finding is supported by evidence of a higher preference for MMT among AYA who are interested in initiating opioid agonist treatment (OAT), which may be explained by perceptions that it is more effective at addressing mental illness and physical pain. 18 Within the study setting, Vancouver, BC, research among adults found self-reported Indigenous identity, recent incarceration, sex work, and injection heroin use were negatively associated with MMT use, while female sex, HIV-positive status, and crack cocaine smoking were positively associated.…”
Section: Introductionmentioning
confidence: 98%